Kualitas Es Krim dengan Kombinasi Penambahan Ekstrak Tulang Ikan Patin Jambal (Pangasius djambal) dan Ekstrak Kacang Gude (Cajanus cajan): Quality of Ice Cream with a Combination of Jambal Catfish (Pangasius djambal) Bone Extract and Pigeon Pea Bean (Cajanus cajan) Extract - Putra, Libertus Anggit Martini Lunggono; Swasti, Yuliana Reni; Pranata, Franciscus Sinung (Faculty of Agricultural Technology, University of Jember, 2024)
Ice cream is a frozen food processed using a stabilizer, fat milk, and protein. It has a soft texture that can survive at room temperature. The bones of jambal catfish (Pangasius djambal) have collagen fibers, which are used to make gelatin as a stabilizer and emulsifier; gude or pigeon pea beans (Cajanus cajan) contain high protein that can be used to improve the quality of protein in ice cream. This research was conducted to determine the quality of ice cream with jambal catfish bone extract and pigeon pea bean extract added, which was seen from a chemical, physical, and microbiological point of view, as well as the acceptability of ice cream for consumption, besides this research also determine the right combination of using jambal catfish bone extract as a stabilizer to replace carboxy methyl cellulose (CMC) and pigeon pea bean extract in improving the quality of ice cream. This research was conducted using a completely randomized design (CRD) with 4 combination treatments of adding jambal catfish bone extract and pigeon pea bean extract i.e., 0:0% (control/K), 0.25:50% (A); 0.5:50% (B) and 0.75:75% (C). The results showed that the best quality of ice cream by the addition of 0.5% jambal catfish bone and 50% pigeon pea bean extract (B) with the protein content of 5.95%, lipid content of 17.48%, total solid of 22.39%, overrun value of 68.00%, melting rate value of 16.95%, total microbes (total plate count) of 2.46 log10 colony/gram, and negative of Salmonella sp. This research is beneficial in replacing synthetic emulsifiers and stabilizers with natural ingredients and increasing the use of plant-based ingredients to increase ice cream protein. Keywords: collagen bone, emulsifier, ice cream, pigeon pea bean extract, stabilizer